2020
DOI: 10.1007/s00784-020-03673-y
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of autotransplanted teeth including an evaluation of a novel surgical technique

Abstract: Objectives To assess survival rates and frequency of complications for immature and mature autotransplanted teeth after at least 1 year in function. Materials and methods All consecutive patients who had undergone tooth autotransplantation between 2000 and 2018 were invited to a clinical and radiographic follow-up examination. First, survival rates were calculated on the basis of a phone inquiry. A clinical follow-up examination allowed for the calculation of the success rate, i.e., absence of any potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…Regarding the technique of autotransplantation of mature teeth, the extraoral root-end resection of teeth with complete root formation showed promising outcomes for transplants, especially with a single root canal and uncomplicated root morphology [ 16 ]. For formation of a transplant cavity, a donor tooth replica was fabricated before surgery using 3D printer machine [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the technique of autotransplantation of mature teeth, the extraoral root-end resection of teeth with complete root formation showed promising outcomes for transplants, especially with a single root canal and uncomplicated root morphology [ 16 ]. For formation of a transplant cavity, a donor tooth replica was fabricated before surgery using 3D printer machine [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the total success rates of autotransplantation were 94% with the open apex teeth and 84% with closed apex groups [ 14 ]. The other retrospective study showed 92% of the survival rate of the immature root form-autotransplanted teeth for midterm length [ 15 ]. In this study, the authors utilized the enamel matrix derivatives (EMD) to apply the root surface to enhance the healing process if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A long‐term follow‐up study showed tooth transplantation success rates of over 90% for patients aged younger than 30 years and 80% for patients aged older than 30 years, with long‐term outcomes of more than 20 years (Tsukiboshi et al, 2019). In another study, immature and mature auto‐transplanted teeth yielded a 91.4% survival probability after a median follow‐up period of 3.4 years, with 62.5% of the tooth showing non‐adverse findings (Raabe et al, 2021).…”
Section: Clinical Aspects Of Tooth Transplantation and Replantationmentioning
confidence: 99%